Analisis Respon Siswa dan Sikap Peduli Lingkungan dalam Pelaksanaan Program Adiwiyata di SDN Jatimalang - Istiqomah, Hidayatul; Sugiyono, Sugiyono; Erviana, Lina (Scholarly Journal of Elementary School, 2022)
The Adiwiyata Program is a school program that aims to create the responsibility of school residents in protecting and managing the environment to support sustainable development. The objectives of this study to describe: 1) the implementation of the Adiwiyata program in SDN Jatimalang; (2) student’s response in the implementation of the Adiwiyata program; (3) the student's environmental care attitude in the implementation of the Adiwiyata program. This research was a qualitative research which used qualitative descriptive methods qualitative. The research subjects were the fifth grade students of SDN Jatimalang. Data collection techniques included documentation, observation, interviews, and questionnaires. Data validation used triangulation technique and data sources. Data analysis used a qualitative descriptive of Miles and Huberman technique, including data reduction, data display, and conclusion. The results showed that: (1) The implementation of the Adiwiyata program in SDN Jatimalang can be carried out well and has been done with the initial planning stages. The implementation of the Adiwiyata program fulfills two aspects: environmental-based school curiculum aspects and participatory-based activities; (2) Student’s response in the implementation of the Adiwiyata program in SDN Jatimalang showed the result of having good responses with a precentage of 72%; (3) The environmental care attitude in the implementation of the Adiwiyata program in SDN Jatimalang showed the result of having good attitudes with a precentage of 78%.